2009
DOI: 10.1152/ajprenal.00125.2009
|View full text |Cite
|
Sign up to set email alerts
|

The instructive role of metanephric mesenchyme in ureteric bud patterning, sculpting, and maturation and its potential ability to buffer ureteric bud branching defects

Abstract: Nigam SK. The instructive role of metanephric mesenchyme in ureteric bud patterning, sculpting, and maturation and its potential ability to buffer ureteric bud branching defects. Am J Physiol Renal Physiol 297: F1330-F1341, 2009. First published September 2, 2009 doi:10.1152/ajprenal.00125.2009.-Kidney organogenesis depends on reciprocal interactions between the ureteric bud (UB) and the metanephric mesenchyme (MM) to form the UB-derived collecting system and MM-derived nephron. With the advent of in vitro sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…4d), reminiscent of the recombination of cultured isolated UB with MM. [11][12][13]43 Thus, cultured cells derived from the UB can, in this system, induce a mesenchymal-to-epithelial transition in the isolated MM. The E-cadherin-positive/DB-negative MM-derived tubule appeared continuous with the DBpositive/E-cadherin-positive UB-cell-derived structure.…”
Section: Rosines Et Almentioning
confidence: 87%
See 1 more Smart Citation
“…4d), reminiscent of the recombination of cultured isolated UB with MM. [11][12][13]43 Thus, cultured cells derived from the UB can, in this system, induce a mesenchymal-to-epithelial transition in the isolated MM. The E-cadherin-positive/DB-negative MM-derived tubule appeared continuous with the DBpositive/E-cadherin-positive UB-cell-derived structure.…”
Section: Rosines Et Almentioning
confidence: 87%
“…MMs isolated from day 13 embryonic kidneys as previously described [11][12][13] were placed directly onto a cell-culturetreated plate and cultured for 5 days in the growth medium supplemented with 50 ng/mL of FGF2 and 10 ng/mL transforming growth factor-a, which support MM survival. 9 The MM cells were then trypsinized and placed on new plates and used for the experiments.…”
Section: Generation Of the Primary MM Cell Linementioning
confidence: 99%
“…In the bovine metanephros, KIT is strongly expressed in the epithelial cells which face the mesenchymal cells at the tip of the branching ureteric bud and which are a site of intense reciprocal epithelial-mesenchymal interactions (Shah et al 2009). The presence of KIT at the tips of the ureteric bud clearly precedes the appearance of KIT in other epithelia of the developing metanephros and, in particular, the expression of SCF, which in contrast to mice is not detected at the tips of the bovine ureteric buds (Schmidt-Ott et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…38 In pregnant C57BL/6J mice, the contractile response of isolated umbilical arteries to ANG II is increased in the presence of the AT2R inhibitor, PD 123319, 46 thus supporting a vasodilatory role for AT2Rs. In contrast, recent studies in isolated umbilical arteries removed from pregnant and non-pregnant women showed that ANG II induced vascular contractions were not altered in the presence of AT2R inhibition.…”
Section: Discussionmentioning
confidence: 98%